Facilitators and barriers to the regulation of medical cannabis: a scoping review of the peer-reviewed literature - Mohammad Ali Ruheel; Zoya Gomes; Sana Usman; Pargol Homayouni; Jeremy Y. Ng (BMC, 2021)
Abstract Background In recent decades, several political, legislative, judicial, consumer, and commercial processes around the world have advanced legalization efforts for the use of medical cannabis (MC). As the use of MC evolves through legislative reform, with an increase in public acceptance and therapeutic potential, a need exists to further investigate the facilitators and barriers to MC regulation. Methods A scoping review was conducted to identify the facilitators and barriers associated with the implementation of MC regulations. MEDLINE, EMBASE, AMED and PsycINFO databases were systematically searched; no restrictions were placed on geographic location/jurisdiction. Eligible articles included those that evaluated the MC regulatory framework of one or more countries. Results Twenty-two articles were deemed eligible and included in this review. Themes identified include: (1) effects of conflicts, mindset, and ideology of state population, (2) the use of comparisons to analyze MC regulation, and (3) the need for more knowledge, advice, and empirical/clinical evidence to inform future MC policies. Conclusion Policymakers should be aware of facilitators to the MC regulation implementation process, such as the influence of state and federal congruence, increased transparency, and the incorporation of stakeholder concerns, in order to effectively respond to a growing societal acceptance of MC and its use among patients. Given a comprehensive understanding of these influential factors, policymakers may be better equipped to meet the consumer and commercial demands of a rapidly evolving MC regulatory environment.